Axiological aspects of law and legal culture of Kazakh society (Journal of actual problems of jurisprudence, 2018)
This article is devoted to analysis of civil society legal culture. The purpose of the article is to highlight valuable reference points of legal culture of the Republic of Kazakhstan in the process of democratic state development. This article is based on research of Kazakhstan and foreign authors on the nature of law, legal culture, its value orientations in the formation of civil society and the rule of law in the Republic of Kazakhstan. The article discusses issues related to the formation of civil society, are different definitions of this phenomenon. It concludes that the main principle of civil society advocates free and comprehensive development of the individual in society, and that civil society starts with the appearance of the citizen as a free member of society who is aware of its purpose, endowed with a set of rights and freedom and the duty of responsibility for their actions to the society.Key words: legal culture, legal ideology, legal psychology, culture, democratic state, civil society, state, society, legal consciousness, democratic state and its values.